Larvae of Ancyronyx Erichson, 1847 (Insecta: Coleoptera: Elmidae) from Sulawesi, using DNA sequences for the assignment of the larval stages - Freitag, Hendrik; Kodada, Ján (Zootaxa, 2017)
We describe the immature stages of six Ancyronyx (Spider Riffle Beetles) species from Sulawesi: A. henningi Freitag & Kodada, 2017; A. longiparamerus Freitag & Kodada, 2017; A. skalei Freitag & Kodada, 2017; A. schoedli Freitag & Kodada, 2017; A. tobada Freitag & Kodada, 2017 and A. toraja Freitag & Kodada, 2017. The larvae were assigned to adults by comparison of their Cox1 gene fragment (mtDNA) which was amplified, sequenced and aligned with the corresponding locus of identified adults. The larvae are illustrated with habitus photographs and SEM micrographs.